Beban Ganda Perempuan: Penguatan Ekonomi Perempuan Melalui Inklusi Keuangan Syariah di Minangkabau - Novia Nengsih (LPPM IAIN Parepare, 2020)
This study aims to analyze double burden and its relation to woman’s economic strengthening. The times have transformed woman’s thinking and movements that they not only function in the domestic sphere but also in the public sphere. This research is field research with qualitative analysis conducted in Padang and involved female costomers of sharia bank X. This study proves that the double burden of woman does not hinder women’s economic strengthening. Woman who experience double burdens can strengthen their economy if they are given access to finance through Islamic financial inclusion.